Cartilage reconstruction using self-anchoring implant with functional gradient - Laurenti,Karen Cristina (2014)
This study presents an innovative and original biomaterial designed to substitute for articular cartilage and mimic its mechanical behavior, including elastic cushioning and the characteristics of fiber-reinforced gel. The material was composed of polyurethane and bioglass microfiber 45S5. It was designed to present a tribological surface to the cartilage of the tibial plateau, and to convert over a functional gradient to an osteointegrable region for self-anchorage to the subchondral bone. The biomaterial samples showed no toxicity and promoted cell spreading. Subsequent in vivo studies in rabbits demonstrated the formation of a rigid structure similar to bone trabeculae in the distal region of the tribological surface of the implant. The tribological surface of the proximal region showed a fibrocartilaginous tissue with highly vascularized chondrocytes, thus validating the proposed concept for the design of the implant incorporating a functional gradient and auto-stability.